Methods of long-term planning and forecasting : proceedings of a conference held by the International Economic Association at Moscow - Khachaturov, T. S.; International Economic Association (London : Macmillan : New York : distributed by Halsted Press, 1976)
This book emphasized the necessity for starting work on a long time planning for the national economic development of the USSR
Includes bibliographical references and index.
oo 16/8/18
Loans
Keywords: Forecasting---Methods; Economic forecasting; Economic policy; Planning; Europe, Eastern